Mood Responses and Regulation Strategies Used During COVID-19 Among Boxers and Coaches - Roberts, Reece J.; Lane, Andrew M. (Frontiers in Psychology, 2021)
The COVID-19 pandemic brought unprecedented changes to daily life and in the first wave in the UK, it led to a societal shutdown including playing sport and concern was placed for the mental health of athletes. Identifying mood states experienced in lockdown and self-regulating strategies is useful for the development of interventions to help mood management. Whilst this can be done on a general level, examination of sport-specific effects and the experience of athletes and coaches can help develop interventions grounded in real world experiences. The present study investigated perceived differences in mood states of boxers before and during COVID-19 isolation in the first lockdown among boxers. Boxing is an individual and high-contact sport where training tends to form a key aspect of their identity. Boxers develop close relationships with their coach and boxing. Hence boxers were vulnerable to experiencing negative mood, and support via the coach was potentially unavailable. Participants were 58 experienced participants (44 boxers, male n = 33, female n = 11; 14 boxing coaches, male n = 11, female n = 3). Boxers completed the Brunel Mood Scale to assess mood before COVID-19 using a retrospective approach and during COVID-19 using a “right now” time frame. Boxers responded to open-ended questions to capture mood regulation strategies used. Coaches responded to open ended questions to capture how they helped regulate boxer’s mood. MANOVA results indicated a large significant increase in the intensity of unpleasant moods (anger, confusion, depression, fatigue, and tension) and reduction in vigor during COVID-19 (d = 0.93). Using Lane and Terry (2000) conceptual framework, results showed participants reporting depressed mood also reported an extremely negative mood profile as hypothesized. Qualitative data indicated that effective mood-regulation strategies used included maintaining close coach-athlete contact and helping create a sense of making progress in training. When seen collectively, findings illustrate that mood state responses to COVID-19 were severe. It is suggested that that active self-regulation and self-care should be a feature of training programmes to aid coaches and boxers in regulating mood when faced with severe situational changes.